'Sharing the space' in the agricultural knowledge and innovation system: multi-actor innovation partnerships with farmers and foresters in Europe. Issue 4 (8th August 2021) - Fieldsend, Andrew F.; Cronin, Evelien; Varga, Eszter; Biró, Szabolcs; Rogge, Elke
ABSTRACT: Purpose: Networks and partnerships are commonly-used tools to foster knowledge sharing between actors and organisations in the Agricultural Knowledge and Innovation System (AKIS), but in Europe the policy emphasis on including users, such as farmers and foresters, is relatively recent. This paper assesses user involvement in a diverse set of European Union (EU)-funded and non-EU (formal and informal) multi-actor partnerships. Design/methodology/approach: A review of 200 projects and other partnerships including farmers and foresters, drawn from an integrated database of several thousand such examples, assessed the types of innovation challenges tackled, solutions proposed, innovation supported, parameters of actor participation and the expectations of success in each example. Findings: All the reviewed policy instruments, not just those funded in the frame of the EIP-AGRI, can be used to involve users in co-innovation in agriculture, forestry and related value chains. Practical implications: The EIP-AGRI is just one part of a complex matrix of multi-actor co-innovation activities involving farmers and foresters in Europe. Interlinking of innovation programmes and more effective targeting of these programmes at groups of actors, especially users, who are currently not sufficiently engaged are worthy aspirations. Theoretical implications: Any analysis of co-innovation involving users must recognise the existence of a multiplicity (projects, non-project activities, formal and informal) of multi-actor approaches. Originality/value: This research used a common methodology to review several forms of multi-actor partnerships involving users and other actors. Our data suggest that many of these are effective methods of supporting co-innovation and are, therefore, 'sharing the space' within the AKIS.